Adverse drug reaction profile at psychiatry outpatient department of a tertiary care centre - Gawali, Ujwala P.; Kesari, Harshad V.; Gawand, Komal S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Monitoring adverse drug reactions (ADRs) helps in alerting physicians and developing strategies to prevent and minimize the risk of developing ADRs. Data regarding pattern of ADRs due to psychotropic medications is scanty. Hence, the study was planned to assess ADRs among psychiatry outpatients of a tertiary care hospital in Maharashtra. Methods: A prospective, observational study was conducted in psychiatry outpatient department of a tertiary care centre for 3 months. Cases were enrolled by active and passive surveillance after obtaining informed consent. Demographic details, adverse event details, history of medications were recorded. Pattern of ADRs was studied according to demographic parameters, drug class, organ system affected, causality (WHO - Uppsala Monitoring Centre Scale) and severity (modified Hartwig and Siegel Scale). Results: Out of total 1200 patients screened, 77 qualified the inclusion and exclusion criteria and 92 ADRs were reported; overall incidence rate of 6.41%. Maximum ADRs were reported in the age group of 31- 40 years. 63.63% subjects received more than 2 psychotropic drugs. Among 24 types of ADRs observed, tremor (13.04%) was the commonest, closely followed by somnolence. Antipsychotics (45.65%) were most frequently incriminated and central nervous system (46.73%) the most often affected. Trifluoperazine (11.96%) was the commonest drug, followed by olanzapine and haloperidol (10.53% each). Causality analysis yielded 66 ADRs as “probable” and on severity analysis 80.43% were mild. Conclusions: The study provides an insight into pattern of ADRs in psychiatry outpatients. It is prudent to communicate this to treating physicians as well as counsel patients (and caregivers). Initiatives and concerted efforts involving all stakeholders in healthcare can go a long way in decreasing drug-related morbidity and health costs.